Middleman covert channel establishment based on MORE routing protocol using network coding in ad hoc networks - Akhtari, Sara; Moghim, Neda; Mahdavi, Mojtaba (International journal of communication systems, 2020)
Summary Covert channels have been recently the subject of the study in both creation and countermeasure aspects. There are many different ways to embed the covert data in network standards and protocols, especially in wireless networks. MORE (MAC‐independent opportunistic routing) is an opportunistic routing protocol which uses networks coding to enhance routing performance by reducing the repetitions. This protocol can be a suitable medium for covert channel establishment. A middleman covert channel establishment method is proposed in this paper over MORE routing protocol and with the use of network coding. Hidden data are transferred through packet's payload bytes. Covert sender manipulates coding mechanism by calculating packets' coefficients instead of random selection. The proposed covert channel provides the average throughput of 218 and 231 bps, using two different data length approaches which is relatively a good comparing to the previous network layer covert channels. The proposed covert channel is also a covert storage channel and cannot be removed or restricted. Effect of different network characteristics on the proposed method's capacity and security is investigated by a simulation study, and the results are discussed. In this paper, a middleman covert channel establishment method is proposed over MORE routing protocol. Hidden data are transferred through the packets' payload and by calculating the packets' coefficients instead of random selection. The proposed covert channel provides the average throughput of 218 and 231 bps in two different data length approaches, which is a good performance comparing with the previous network layer covert channels. The proposed covert channel is a covert storage channel and cannot be removed or restricted.